Promoting the development of teacher professional knowledge: Integrating content and pedagogy in teacher education. (October 2018) - Evens, Marie; Elen, Jan; Larmuseau, Charlotte; Depaepe, Fien
Abstract: The study investigates the explicit and integrated presentation of pedagogical content knowledge (PCK), pedagogical knowledge (PK), and content knowledge (CK) in teacher education. We compare learning environments to study whether only presenting PK and CK is sufficient for PCK development, whether only presenting PCK is sufficient for PK and CK development, and whether PCK development is affected by integrating PCK, PK and CK. We find that only presenting two knowledge domains to students is insufficient to develop the third one, and integrating knowledge domains does not impact PCK development. Highlights: Only PK and CK instruction is insufficient to develop PCK in teacher education. Only PCK instruction is insufficient to develop PK and CK in teacher education. Explicit presentation of PCK, PK and CK leads to optimal professional knowledge. Integrated instruction leads to similar PCK development as segregated instruction.